Extract and fraction of Cassia occidentalis L. (a synonym of Senna occidentalis) have osteogenic effect and prevent glucocorticoid-induced osteopenia. (10th May 2019) - Pal, Subhashis; Kumar, Padam; Ramakrishna, Eppalapally; Kumar, Sudhir; Porwal, Konica; Kumar, Brijesh; Arya, Kamal R.; Maurya, Rakesh; Chattopadhyay, Naibedya
Abstract: Ethnopharmacological relevance: Cassia occidentalis L., a synonym of Senna occidentalis (belongs to Caesalpiniaceae family) is an annual plant. Pursuing a lead from a folk practice prevalent since the late nineteenth century in Andhra Pradesh, a Southern state of India, of use of Cassia occidentalis leaf and stem for treating patients with fracture and bone diseases, we have not only confirmed its fracture healing activity but also demonstrated efficacy in preventing glucocorticoid-induced osteoporosis (GIO), the commonest form of medication-induced bone loss caused chiefly due to impairment of bone formation. Aim of the study: In the present work, the effects of extract and fraction of leaf and stem of Cassia occidentalis was investigated in fracture healing and GIO models of rat. The study also aimed to identify osteogenic compounds from this plant. Materials and methods: Ethanolic extracts from leaf and stem of Cassia occidentalis were prepared and their efficacy tested in rat femur osteotomy (fracture healing) model. Subsequently, a butanolic fraction was prepared and osteogenic efficacy compared with the ethanolic extract, and upon finding the former to be more potent, its osteogenic effect was studied in details in GIO model. Chemical finger-printing and isolation of ten pure compounds were done to assess their osteogenic effect in rat primary osteoblast cultures. Results: Ethanolic extract of stem was more effective than the leaf extract in enhancing bone regeneration at the site of osteotomy. Further, butanolic fraction of the ethanolic extract of stem was more effective than the later in bone regeneration at the femur osteotomy site and in preventing bone loss in GIO model. The mechanism of skeletal preservation involved stimulation of new bone formation and inhibition of bone resorption. As many as six osteogenic compounds were isolated out of which apigenin-6 C -glucopyranoside was most effective in vitro. Conclusion: Our study found that a standardized extract of an ethanolic extract and its butanolic fraction from the stem of Cassia occidentalis has osteogenic as well as anti-resorptive effects, resulting in the protection against glucocorticoid-induced bone loss. Our results contribute towards validation of the traditional use of Cassia occidentalis in fracture healing and also suggest its beneficial use in GIO for which clinical trials are warranted. Graphical abstract: fx1